Creative photocopying Using the photocopier for crafts, design and interior decoration - Walton, Stewart
A collection of ideas for using photocopied images in craft work and interior decoration, twenty-seven of which are presented as step-by-step projects. It also acts as a source book in that many of the images are included on detatchable sheets at the back of the book.